2018
DOI: 10.1099/mgen.0.000233
|View full text |Cite
|
Sign up to set email alerts
|

The resistomes of six carbapenem-resistant pathogens – a critical genotype–phenotype analysis

Abstract: Carbapenem resistance is a rapidly growing threat to our ability to treat refractory bacterial infections. To understand how carbapenem resistance is mobilized and spread between pathogens, it is important to study the genetic context of the underlying resistance mechanisms. In this study, the resistomes of six clinical carbapenem-resistant isolates of five different species – Acinetobacter baumannii, Escherichia coli, two Klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa – were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 108 publications
(82 reference statements)
1
36
0
Order By: Relevance
“…17 This cluster also contains 2 strains from stool samples from a Chinese (GCF_000313255.1) and a Swedish subject (GCF_003194305.1). 18,19 Interestingly, the remaining 2 isolates, both recovered from the patient biopsy sample of patient W19, were assigned to a distinct branch within the P mirabilis lineage, along with an isolate recovered from a stool sample as part of the National Institutes of Health Human Microbiome Project.…”
Section: All Of the Clinical Isolates Recovered From Thementioning
confidence: 99%
See 1 more Smart Citation
“…17 This cluster also contains 2 strains from stool samples from a Chinese (GCF_000313255.1) and a Swedish subject (GCF_003194305.1). 18,19 Interestingly, the remaining 2 isolates, both recovered from the patient biopsy sample of patient W19, were assigned to a distinct branch within the P mirabilis lineage, along with an isolate recovered from a stool sample as part of the National Institutes of Health Human Microbiome Project.…”
Section: All Of the Clinical Isolates Recovered From Thementioning
confidence: 99%
“…The genome assemblies for all 24 clinical isolates were annotated using Prokka, RAST, and National Center for Biotechnology Information. 19,20 For genomic comparisons, the isolates and publicly available genomes were then uploaded to the software platform EDGAR 21 to determine a core, shared and accessory genome. The average nucleotide identity scores between the orthologs present in a "core genome" from all 57 P mirabilis genomes were also calculated using EDGAR, and a matrix of average nucleotide identity scores generated using RStudio.…”
Section: Genomic and Plasmid Dna Extraction And Sequencingmentioning
confidence: 99%
“…In combination with CRISPR/Cas9 restriction, we can obtain information about plasmid size, resistance gene location, and barcode in the same experiment [17]. For the characterization of plasmids, we have previously demonstrated that the ODM results correlate very well with NGS analysis [14,[18][19][20]. We have also showed its usefulness in tracking possible transmission routes in nosocomial outbreak investigations, in a neonatal polyclonal outbreak due to CTX-M-producing bacteria in Sweden, and in an ESBL E. coli ST410 outbreak in a clinical setting in Ethiopia [12,20].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrio ssp. and Xanthomonas ssp., or on conjugative elements, as is common for in pathogens such as Escherichia coli and Salmonella enterica [7,8]. Since integrons enable incorporation of a wide range of genes, they have been suggested to play a major role in the adaptation and evolution of many forms of bacteria [9][10][11].…”
Section: Introductionmentioning
confidence: 99%